2018
DOI: 10.1166/jnn.2018.14316
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Oxidative and Antibacterial Self-Healing Edible Polyelectrolyte Multilayer Film in Fresh-Cut Fruits

Abstract: The consumption of fresh-cut fruits is limited because of the oxidation browning and pathogenic bacteria's growth on the fruit surface. Besides, crack of the fresh-keeping film may shorten the preservation time of fruit. In this work, polyelectrolyte multilayer (PEM) film was fabricated by layer-by-layer (LBL) electrostatic deposition method. The film was made by carboxy methylcellulose sodium (CMC) and chitosan (CS). The as-prepared PEM film had good anti-oxidative and antibacterial capability. It inhibited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…e phenomenon was presumably related to the swelling behavior of the chitosan coating in the humid atmosphere, or related to the crosslinking between CMC and chitosan which results in a formation of a more loosely packed poriferous matrix rather than of a denser one and enlarges the intermolecular space and promotes the transport of water molecules in the assembly structure. It was consistently reported that the stratified structure and linear increase in the absorbance verified a linear increase in coating thickness [28]. In addition, the mechanical properties of the LBL assembly were significantly improved, in terms of both strength and elasticity (p < 0.05, Table 1).…”
Section: Assembly Propertiessupporting
confidence: 54%
“…e phenomenon was presumably related to the swelling behavior of the chitosan coating in the humid atmosphere, or related to the crosslinking between CMC and chitosan which results in a formation of a more loosely packed poriferous matrix rather than of a denser one and enlarges the intermolecular space and promotes the transport of water molecules in the assembly structure. It was consistently reported that the stratified structure and linear increase in the absorbance verified a linear increase in coating thickness [28]. In addition, the mechanical properties of the LBL assembly were significantly improved, in terms of both strength and elasticity (p < 0.05, Table 1).…”
Section: Assembly Propertiessupporting
confidence: 54%
“…Moreover, the addition of chitosan endowed the fabricated PEM coating with the free radical scavenging activity of 78.62%, and the antibacterial capacity of 100% and 95.48% against Salmonella and E. coli, respectively. 31 A similar PEM coating was manufactured from CMC, chitosan, and CaCl 2 for the storage of lemons under refrigerated conditions for up to 60 days. 115 It was revealed that the increased thickness of coating contributed to the higher cross-linking degree and led to the enhanced gas barrier, mechanical, and self-healing properties.…”
Section: Self-healing Coatings For Food Packagingmentioning
confidence: 99%
“…Reversible electrostatic interactions can be initiated between the charged polymers and ions, 52 polyelectrolytes, 64 polyampholytes, 65 and zwitterionic fusions, 66 resulting in the formation of self‐healing films, 31 hydrogels, 12 and aerogels 67 . For instance, a polyelectrolyte multilayer (PEM) film with self‐healing ability was constructed from polydopamine and SA by layer‐by‐layer (LBL) assembly 68 .…”
Section: Self‐healing Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early 1990's, Decher et al developed a simple but effective way to prepare ultrathin polyelectrolyte multilayer film via layer-bylayer (LbL) assembly [16,17]. Polyelectrolyte multilayers (PEMs) have received extensive attention in the past decade due to their promising applications in very diverse fields [18] such as chemical sensors [19] optical devices [20], biosensors [21] light-emitting diodes [21], biomedical coatings [22][23][24], Antioxidative and Antibacterial Self-Healing [25]. The driving force for the LbL assembly of oppositely charged polyelectrolyte chains is mainly attributed to the electrostatic interactions [17].…”
Section: Introductionmentioning
confidence: 99%